The Middle English suffix -ish: Reasons for decline in productivity - Ciszek, Ewa (Adam Mickiewicz University, 2012)
The aim of the present paper is to investigate the reasons for the significant decline in both the frequency and productivity of the suffix -ish in Middle English. The major factors responsible seem to be the growing popularity of the of + Noun phrases as well as the competition among -ish and other suffixes. The analysis will be preceded with the introduction of some essential facts concerning the semantic development and productivity of the OE suffix -isc in Middle English.